A NEW GENUS OF SMINTHURIDS - TELLEZ, C; BONET, FEDERICO (Instituto Cardiología, CD MEXICO, DF, MEX, 1947)
A comparative study of the structures on which the systematics of this family is based indicates: (1) Characters until now regarded of generic rank, such as direction of head, limits between trunk segments, and segmentation of limbs, do not differ signifi
REV SOC MEX HIST NAT
Keywords: NEW GENUS, SMINTHURIDS; CIENCIAS DE LA VIDA; BIOLOGIA DE LOS INSECTOS (ENTOMOLOGIA); MORFOLOGIA DE LOS INSECTOS